The effectiveness of using circle geometry board (CG-Board) strategy in learning circle geometry towards secondary students performance / Dr. Raja Lailatul Zuraida Raja Maamor Shah, Reena Nancy Stephen Benjamin and Raja Noor Farah Azura Raja Maamor Shah - Raja Maamor Shah, Raja Lailatul Zuraida; Stephen Benjamin, Reena Nancy; Raja Maamor Shah, Raja Noor Farah (Universiti Teknologi MARA, Kedah, 2019)
Geometry is one of the branches of mathematics that is taught to students in secondary school in Malaysia. One of the topics learn by the students, is the Circle Geometry concepts. Students have problems in visualizing the parts of the circle and the angles subtended in a circle, determining the angles subtended at the center and the radius of the sector. It shows that students are unable to link more than one concept of circle geometry presented in a circle. During teaching and learning session, the students observe silently and memorize the geometrical concept given by the teacher and the students too, rely on their text book to learn geometry. The development of CG-Board is to give students and teachers another alternative teaching and learning methods besides using innovative geometry software. The theory used in developing the CG-Board and the activity book is Van Hiele’s Theory of Geometric Thought. The development of the CG-Board as a manipulative helps teachers to create a more meaningful learning for students as they can see the relevance. The secondary students will be able to comprehend an abstract idea of Circle Geometry concepts easily through exploration and investigation activities in drawing the conclusion of the concepts they learn. Tests through quasi-experimental design were done and students have shown improvement in their knowledge in the Circle Geometry concept.